Recycled concrete and demolition waste aggregate in concrete - Lloyd, Natalie; Van Der List, K.; Re, N. (2013)
Demolition and construction waste may be used as a partial replacement of virgin coarse aggregate in concrete, although the current industry uptake of this is low despite sustainability advantages. The variability of demolition and concrete waste is cited as a reason for its low usage rates. This research examined the variability of the waste from different suppliers over time. The recycled aggregates were also compared to each other by determining their bulk density, angularity number and flakiness index. Concrete mixtures where then prepared with partial replacement of the virgin coarse aggregate in the order of 30-50%. The compressive and tensile strengths, water absorption and apparent permeable voids of these mixtures were tested and the results compared to a base mixture made using only natural aggregates. The strength of the concrete; compressive and tensile decreased with the addition of recycled aggregate. The grading of the aggregate was found to have the most impact on the concrete strength. The inclusion of the recycled aggregate increased the water absorption and permeable voids. The 30% replacement has the greatest potential for application.